Zakat as an Instrument for Alleviating Poverty and Income Gap - Ahmad Rifa’i; Abdullah; Mahatir Muhammad Sidebang (Penerbit Merdeka Kreasi, 2024)
Zakat is one of the important instruments in the Islamic economic system that has a social and economic function in realizing fair distribution and community welfare. In the midst of increasing poverty and income inequality, especially in developing countries such as Indonesia, optimizing the role of zakat is very relevant and urgent. This study aims to examine the extent to which zakat plays an effective instrument in alleviating poverty and reducing income gaps, as well as how the zakat management mechanism can be improved to be more productive and have a long-term impact. This study uses a descriptive qualitative approach with interview, observation, and documentation methods of zakat institutions, mustahik, and Islamic economic experts. The results of the study show that productive zakat, if managed in a targeted and accountable manner, can encourage the empowerment of mustahik economies and increase their income significantly. In addition, zakat is also able to reduce the accumulation of wealth in the hands of a few people and create a fairer distribution of income. The main obstacles lie in weak governance, lack of zakat literacy, and the lack of a national integration system based on mustahik and muzakki data. The novelty of this research lies in the integrative approach of zakat as an alternative economic policy that is not only spiritually based, but also able to synergize with national development strategies in overcoming poverty and inequality. With modern and transparent zakat management, zakat has the potential to become an applicable Islamic economic solution.